Clarification of the concept and essence of the administrative and legal policy of the state - Kramarchuk , Svitlana; Kramarchuk , Nazar (Actual problems of law (Aktual'ni problemi pravoznavstva), 2025)
The article is dedicated to clarifying the concept and essence of the administrative and legal policy of the country in the context of modern challenges facing public administration. The authors examine existing approaches to defining administrative and legal policy in academic literature. Based on the conducted analysis, a refined definition of the concept of administrative and legal policy is proposed, which will more clearly outline its role in the contemporary management process and the provision of the legal foundations for the functioning of the state. Thus, administrative and legal policy is defined as a set of measures and legal norms adopted by state authorities to regulate public relations in the field of public administration. It is emphasized that administrative and legal policy determines the main directions and principles of the activities of state authorities and local self-government bodies, aimed at ensuring law and order, adherence to legality, and the effective functioning of the state apparatus. The article also explores the key aspects of this concept, focusing on its interconnection with public law, the functions of state authorities, and the mechanisms of their interaction with citizens. For a more detailed study of the essence of administrative and legal policy, the article examines and proposes its own definition of administrative and legal relations. Special attention is given to defining the main characteristics and functions of administrative and legal policy. The fundamental principles of building the administrative and legal policy of the country are explored and defined, which will contribute to ensuring law and order, stability, and the efficiency of public administration.